Efficacy of a chewable tablet containing sarolaner, moxidectin, and pyrantel (Simparica Trio®) in the treatment of sarcoptic mange caused by Sarcoptes scabiei mite infestations in dogs - Csilla Becskei; Julian Liebenberg; Tiago Fernandes; Stasia Borowski; Lina D’Hanis; Sean P. Mahabir (Parasites & Vectors, 2023)
Abstract Background Infestation with Sarcoptes scabiei in dogs is a debilitating disease if left untreated and is transmissible to humans. Two field studies were conducted to confirm the efficacy of orally administered sarolaner in combination with moxidectin and pyrantel (Simparica Trio®) in the treatment of sarcoptic mange in dogs. Methods Client-owned dogs with S. scabiei infestation were enrolled and received 2 monthly treatments. In the first, small-scale study, 12 dogs each were allocated randomly to treatment with either placebo or Simparica Trio®. Skin scrapings to detect live mites and assessment of clinical signs of sarcoptic mange were conducted on Days 0, 14, 30, 44, and 60. Efficacy was calculated based on the percent reduction in arithmetic mean live mite counts relative to placebo. In the second, large-scale study, 75 dogs were allocated randomly to treatment with Simparica Trio® and 37 to treatment with afoxolaner + milbemycin oxime (NexGard Spectra®). Skin scrapings to detect live mites and assessment of clinical signs of sarcoptic mange were conducted on Days 0, 14, 30, and 60. The parasitological cure rate (percentage of dogs without live mites) was determined and non-inferiority of Simparica Trio® to the control product was assessed. Results In the small-scale study, 2 monthly doses of Simparica Trio® resulted in a significant reduction (P ≤ 0.0050) in live S. scabiei mite numbers and provided a 99.2% reduction relative to placebo by Day 60. Clinical signs of sarcoptic mange improved throughout the study in Simparica Trio®-treated dogs. In the large-scale study, the parasitological cure rate on Days 30 and 60 was 97.3% and 100% in the Simparica Trio® group and 91.9% and 100% in the afoxolaner + milbemycin oxime group, respectively. The parasitological cure rate for Simparica Trio® was non-inferior to afoxolaner + milbemycin oxime at both time points. Clinical signs of sarcoptic mange improved throughout the study in both groups. Conclusions Two-monthly doses of Simparica Trio® reduced S. scabiei mite counts by 99.2% relative to placebo in one study and eliminated S. scabiei mites in 100% of dogs in the second study, thus confirming that Simparica Trio® is highly effective in the treatment of sarcoptic mange in dogs caused by S. scabiei var. canis. Graphical abstract